2020
DOI: 10.1111/echo.14589
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the size of cardiac structures in patients with high body mass index

Abstract: Aims Isometric indexation of cardiac structures fails in patients with overweight. The aim of the study was to evaluate the LA indexed volume (LAVOL), left ventricular end‐diastolic diameter (LVEDD), left ventricular mass index (LVMI), and the aortic sinus diameter (AOSD) in healthy subjects with normal and high BMI and find the allometric correction exponent. Methods Four hundred and thirty patients without cardiac pathology were analyzed. Patients were divided into groups: Group I BMI < 24.9 187 patients, Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…Importantly, studies report various ideal height exponents for LAV indexation. Previous reports demonstrate that exponents closer to 1.7–2 are ideal for LAV indexation [ 10 , 11 , 24 ], though other studies report ideal LAV indexation with height exponents closer to 1 [ [25] , [26] , [27] ], and this may represent the inherent variability in ethnicity, as demonstrated in our study. Moreover, previous studies reporting higher exponents likely had a greater proportion of Caucasian/White populations.…”
Section: Discussioncontrasting
confidence: 43%
“…Importantly, studies report various ideal height exponents for LAV indexation. Previous reports demonstrate that exponents closer to 1.7–2 are ideal for LAV indexation [ 10 , 11 , 24 ], though other studies report ideal LAV indexation with height exponents closer to 1 [ [25] , [26] , [27] ], and this may represent the inherent variability in ethnicity, as demonstrated in our study. Moreover, previous studies reporting higher exponents likely had a greater proportion of Caucasian/White populations.…”
Section: Discussioncontrasting
confidence: 43%
“…First, Zong et al found that allometric scaling was superior to conventional isometric indexation in a population of 717 patients with obesity with a mean BMI of 42.2 kg/m2 [ 30 ]. Second, in a paper by Carnavelini et al, a similar conclusion was drawn in 63 patients with mild, and 26 patients with moderate obesity [ 31 ]. Although both studies demonstrated that allometric scaling was superior to isometric scaling, potential supportive data regarding the relation of alternative indexing methods with LA function was not available.…”
Section: Discussionmentioning
confidence: 58%
“… 15 , 16 There are few studies which have shown ideal LAV indexation with height exponents closer to 1. 17 , 18 This differences may be due to ethnic differences seen in the different population studied.…”
Section: Discussionmentioning
confidence: 97%